2023
DOI: 10.1001/jamanetworkopen.2023.23746
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Discontinuation or Change of Selective Serotonin Reuptake Inhibitors in Online Drug Reviews

Abstract: ImportanceSelective serotonin reuptake inhibitors (SSRIs) are a commonly prescribed medication class to treat a variety of mental disorders. However, adherence to SSRIs is low, and uncovering the reasons for discontinuation among SSRI users is an important first step to improving medication persistence.ObjectiveTo identify the reasons SSRIs are discontinued or changed, as reported by patients and caregivers in online drug reviews.Design, Setting, and ParticipantsThis qualitative study used natural language pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…It was apparent from our study that social media data may prove most fruitful for more timely hypothesis generation of new or unexpected adverse events and for detecting reports of mild symptomatic events. Knowledge of mild symptomatic events is difficult to quantify and has been shown through social media to play a role in adherence patterns [107,108] and coping strategies [106]. Future research that uses state-of-the-art NLP methods to identify personal experiences of adverse events from a range of platforms and that can directly capture reports of medication change alongside the reasons for change poses to bring the best return-on-investment for the incorporation of social media data with other traditional data sources.…”
Section: Discussionmentioning
confidence: 99%
“…It was apparent from our study that social media data may prove most fruitful for more timely hypothesis generation of new or unexpected adverse events and for detecting reports of mild symptomatic events. Knowledge of mild symptomatic events is difficult to quantify and has been shown through social media to play a role in adherence patterns [107,108] and coping strategies [106]. Future research that uses state-of-the-art NLP methods to identify personal experiences of adverse events from a range of platforms and that can directly capture reports of medication change alongside the reasons for change poses to bring the best return-on-investment for the incorporation of social media data with other traditional data sources.…”
Section: Discussionmentioning
confidence: 99%
“… 36 , 37 For example, in a recent study, insomnia was found to be one of the most common reasons for treatment discontinuation in patients receiving SSRIs. 38 Available data suggest that rates of treatment-emergent insomnia are lower in patients treated with vortioxetine than in those receiving SSRIs and SNRIs. 36 , 37 In a meta-analysis of TEAEs in 11 short-term, randomized, double-blind, placebo-controlled studies of vortioxetine 5–20 mg/day in patients with MDD, the incidence of insomnia was 2.0–5.1% for vortioxetine versus 4.0% for placebo.…”
Section: Discussionmentioning
confidence: 99%